Full color-tunable vertically stacked quantum dot light emitting diodes for next-generation displays and lighting. Issue 48 (10th December 2020) - Acharya, Krishna P.; Titov, Alexandre; Hyvonen, Jake; Kim, Baek Hyun; Ying, Chen; Holloway, Paul; Lamkin, Mark A.; Guest, Stephen; Ringgenberg, Kyle
Abstract : A full-color tunable vertically stacked EL-QLED is fabricated by separating subpixels with insulating layers and using transparent electrodes. Abstract : We report solution-processed color tunable vertically stacked electroluminescent red, green, and blue quantum dot light emitting diodes (QLEDs). These QLEDs can be independently driven to produce all primary, secondary, and white lights. We have fabricated the device by chemical and electrical isolation of each QLED with transparent polymers and by the use of transparent electrodes. These stacked QLEDs can be used for next-generation display and lighting applications that need high pixel density along with quantum dots' intrinsic benefits such as low turn-on voltage, color purity, and solution processability.